Research on the coupling effect of film thickness and UV aging cycle on the rheological properties and microstructure evolution law of asphalt - Li, Zhe; Wei, Xuefeng; Hou, Gui; Xing, Yadong; Wang, Dengyong (Frontiers in Materials, 2025)
In high-altitude regions, intense ultraviolet (UV) radiation significantly accelerates the aging of road asphalt. However, there is currently a lack of corresponding UV aging standard tests. This study addresses this issue by designing a programmable, adjustable-intensity indoor UV aging test to more accurately simulate the strong UV environment found at high altitudes. This study examines the effects of varying UV aging cycles and asphalt film thicknesses on the rheological properties and micro-aging mechanisms of 90# asphalt. Employing tests such as the dynamic shear rheometer, multi-stress creep recovery, and linear amplitude sweep, the study quantifies the impact of UV aging on asphalt’s high-temperature stability, deformation recovery capacity, and fatigue life. In conjunction with analyses via Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Atomic Force Microscopy (AFM), this research elucidates the evolution of chemical functional groups under UV irradiation, characterizes micro-crack propagation through five distinct stages, and reveals the underlying mechanisms governing changes in ‘bee structures.’ The findings indicate that UV aging significantly increases the asphalt’s high-temperature rutting factor by up to 303% for a 1 mm film after 9 cycles, and decreases its unrecoverable creep compliance by as much as 35.9%. This hardening, however, ultimately impairs its fatigue performance, with fatigue life reduced by up to 25.0%. The thickness of the asphalt film is identified as a crucial factor influencing the depth of aging, with thinner layers undergoing more severe aging. On a microstructural level, FTIR analysis confirmed an increase in carbonyl (IC=O) and sulfoxide (IS=O) functional group indices and a decrease in the aromatic compounds (IAr) index. Concurrently, surface damage progressed from micro-wrinkling to macro-cracking, and the average area of ‘bee structures’ in the most severely aged sample (1 mm-9C) increased by 248% compared to the unaged asphalt. This research provides key theoretical insights and quantitative data support for material selection, durability design, and lifespan prediction of asphalt pavements in areas with intense UV radiation, offering a conceptual framework for developing standardized asphalt aging tests.